URGENSI SUPERVISI PENDIDIKAN DALAM PENINGKATKAN MUTU PENDIDIKAN - teuku darmansyah (Hijri, 2019)
The aim of the education supervision is to improve professional and technical skills for teachers, principals, and other school personnel to make the school's education process more qualified. And most importantly, the supervision of this education is done on the basis of cooperation, and the way more human. SEducation is instrumental in giving ease and helping the headmaster and teachers to develop the optimal potential.Judging by the function of supervisionas follows: (a). As a coordinator he can coordinate teaching and learning programs, the duties of staff members of different activities among the teachers. (b). As a consultant he can provide assistance, together to consult the problems that the teacher experienced both individually and in groups. According to the use of technical supervision. (c) As leader of the group he can lead a stafguru in developing the potential of the group, while developing the curriculum, lesson materials and professional needs of the teachers together. (d). As an evaluator he can help teachers assess the outcome and learning process, can assess the developing uricum. He must also learn to look at himself. Judging from the defendant and its function, the supervision is very important in improving the quality of education, initially supervision only ensures that the teachers perform their duties professionally, of course will ultimately improve the quality of education with Professional teachers in the school. More and more teachers who are guided to become more professional will eat the education.